Towards New Realities: Implications of Personalized Online Layers in Our Daily Lives - Herder, Eelco; Stojko, Laura; Strecker, Jannis; Neumayr, Thomas; Yigitbas, Enes; Augstein, Mirjam (i-com - Journal of Interactive Media, Special Issue on “The Future of Human-Computer Interaction”)

A Lower Bound on the Critical Momentum of an Impurity in a Bose–Einstein Condensate - Hinrichs, Benjamin; Lampart, Jonas (Comptes Rendus. Mathématique)

On the Ergodicity of Renormalized Translation-Invariant Nelson-Type Semigroups - Hinrichs, Benjamin; Hiroshima, Fumio (arXiv:2412.09708)
We present a simple functional integration based proof that the semigroups generated by the ultraviolet-renormalized translation-invariant non- and semi-relativistic Nelson Hamiltonians are positivity improving (and hence ergodic) with respect to the Fröhlich cone for arbitrary values of the total momentum. Our argument simplifies known proofs for ergodicity and the result is new in the semi-relativistic case.

On Lieb–Robinson Bounds for a Class of Continuum Fermions - Hinrichs, Benjamin; Lemm, Marius; Siebert, Oliver (Annales Henri Poincaré)

Non-Fock ground states in the translation-invariant Nelson model revisited non-perturbatively - Hasler, David; Hinrichs, Benjamin; Siebert, Oliver (Journal of Functional Analysis)
Keywords: Analysis

Children’s Information-Related Internet Use at Home: The Role of the Quantity and Quality of Parental Support and Children’s Motivation - Gruchel, Nicole; Kurock, Ricarda; Bonanati, Sabrina; Buhl, Heike M. (Journal of Research in Childhood Education)
Children’s information-related internet use positively affects their acquisition of computer- and information-related skills. Nevertheless, this use still occurs predominantly in the family context. Parents’ support of their children’s internet use can motivate them to use the internet for information-related purposes. However, while parents’ support seems to be important, the quantity and quality of parental support have been shown to have different associations with children’s motivation. Thus, the goal of the current study was to examine the relationship between parents’ support (quantity and quality), children’s motivation to engage in information-related internet use, and children’s actual information-related internet use (practical and school- or learning-related use) using structural equation modeling. In addition, we examined the mediating effects of children’s motivation. Specifically, 492 12-year-old German children answered a paper-and-pencil questionnaire. We found positive associations between the quantity and quality of parents’ support and children’s intrinsic and extrinsic motivation, while only structure-giving support was found to be related to children’s intrinsic motivation. The quantity of support was directly related to children’s school- or learning-related use, while intrinsic motivation was associated with both forms of information-related internet use. Furthermore, we confirmed that children’s motivation is an important mediator in this context. The implications of these findings for parents and children are considered.
Keywords: children's motivation; information-related internet use; quality of parental support; quantity of parental support

Guiding Quality Diversity on Monotone Submodular Functions: Customising the Feature Space by Adding Boolean Conjunctions - Schmidbauer, Marcus; Opris, Andre; Bossek, Jakob; Neumann, Frank; Sudholt, Dirk (Proceedings of the Genetic and Evolutionary Computation Conference, GECCO 2024, Melbourne, VIC, Australia, July 14-18, 2024)

On the Effectiveness of Heterogeneous Ensemble Methods for Re-Identification - Klüttermann, Simon; Rutinowski, Jérôme; Polachowski, Frederik; Nguyen, Anh; Grimme, Britta; Roidl, Moritz; Müller, Emmanuel (International Conference on Machine Learning and Applications, ICMLA 2024, Miami, FL, USA, December 18-20, 2024)

Generalised Kruskal Mutation for the Multi-Objective Minimum Spanning Tree Problem - Bossek, Jakob; Grimme, Christian (Proceedings of the Genetic and Evolutionary Computation Conference, GECCO 2024, Melbourne, VIC, Australia, July 14-18, 2024)

Benchmarking Sentence Embeddings in Textual Stream Clustering with Applications to Campaign Detection - Stampe, Lucas; Stockdiek, Janina Lütke; Grimme, Britta; Grimme, Christian (International Joint Conference on Neural Networks, IJCNN 2024, Yokohama, Japan, June 30 - July 5, 2024)

Wissensmanagement in Feuerwehren skalierbare IT-Architektur für Erweiterung und Austausch - Schultz, Andreas Maximilian; Mozgova, Iryna

Rezension zu: „The Nordic Bible. Bible Reception in Contemporary Nordic Societies“ - Bergmann, Claudia Dorit (tà katoptrizómena – Magazin für Kunst | Kultur | Theologie | Ästhetik 147)

Weather-induced emergency situations: Extreme data in situational awareness and visualisation - Gräßler, Iris; Pottebaum, Jens; Hieb, Michael; Pratzler-Wanczura, Sylvia; Krüger, Oliver; Kruijff, Ivana; Rupp, Nicola (Proceedings of the Days of Security Research 2023)
Extreme weather situations increasingly lead to hazardous situations with high demands on de-cision-making and communication. Weather and impact forecasts serve to prepare for such an emergency situation, and extreme data must be processed during operations. Therefore, extreme data is categorised with reference to global weather data and data from local situation reconnais-sance using sensors carried by mobile robots. A concept is presented in which information quality is explicitly considered in visualization for situational awareness. This extends existing principles of information visualisation with regard to the uncertainty resulting from extreme data. The re-sults are intended to help decision-makers at different management levels to make informed decisions.

Experimentelle und numerische Analyse des Fließverhaltens von hochviskosen Wärmeleitstoffen im Fertigungsprozess - Gröger, Benjamin; Wiebicke, Felix; Koch, Ilja; Gude, Maik; Gilich, Julian; Meschut, Gerson (24. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

N2O oxidized combustion of ethylene: Detailed laminar flame structure and the significance of oxidizer decomposition kinetics for modeling - Hoener, Martin; Bierkandt, Thomas; Shaqiri, Shkelqim; Kasper, Tina (Proceedings of the Combustion Institute)

ADMM-TGV image restoration for scientific applications with unbiased parameter choice - Zietlow, Christian; Lindner, Jörg (Numerical Algorithms)

Vermittlungshorizonte. Erziehungswissenschaftliche Reflexionen über hochschul- und wissenschaftsdidaktische Herausforderungen - Freitag, Christine (Wissenschaftsdidaktik als kritische Kommunikationsanalyse. Ein Sammelband zur Weiterführung eines Gedankens von Ludwig Huber)

Der Briefroman als Medium weiblicher Kritik in der Aufklärung – Einblicke in Caroline Rudolphis »Gemälde weiblicher Erziehung« - Vochatzer, Stefanie (»Debattieren, Opponieren, Protestieren – Interdisziplinäre Perspektiven auf sprachliche Praktiken des Widersprechens«)

Efficient Shape Formation by 3D Hybrid Programmable Matter: An Algorithm for Low Diameter Intermediate Structures. SAND 2024: 15:1-15:20 - Scheideler, Christian; Hinnenthal , Kristian; Liedtke, David Jan

Polylogarithmic Time Algorithms for Shortest Path Forests in Programmable Matter. - Scheideler, Christian; Padalkin, Andreas